“Skeptic Sound” – Manual de identidad visual para casa musicalizadora audiovisual - Seminario Nalvarte, Pablo Daniel (2019)
This document seeks to support the development process of the visual identity and brand guidelines of “Skeptic Sound”, a music studio focused on the filmmaking market and video industry. The project consists in a market study of competitors as well as a benchmarking process (comparison between brands) in order to understand the context of local and international music studios. Likewise, the final stage includes the development of the brand identity manual or "brandbook", which is the result of all research and development in an editorial document. It can provide proper guidelines for a correct brand reproduction, and also to show the value and concept of the brand. Finally, this report presents the discoveries made in the graphic design area during the project and the lessons learned that can contribute as new and useful knowledge.